Pengaruh Penerapan Sistem E-Filling, Pengetahuan Pajak, Dan Sanksi Pajak terhadap Kepatuhan Wajib Pajak Orang Pribadi (Studi Empiris Di KPP Pratama Depok Sawangan 2022) - Jumarso Fajar Setioawan; Ansaril Kambut (Politeknik Negeri Padang, 2024)
This study aims to determine the effect of the application of the E-Filling System, , Tax Knowledge, and Tax Sanctions on Individual Taxpayer Compliance (Empirical Study at KPP Pratama Depok Sawangan 2022). The independent variables used in this study are the application of the E-Filling System, Tax Knowledge, and Tax Sanctions. While the dependent variable used in this study is individual taxpayer compliance. This study uses quantitative research methods with primary data obtained from the results of questionnaires distributed directly to respondents. The sampling technique used in this study is purposive sampling and this study uses multiple linear regression. The results of this study indicate that tax sanctions have a positive and significant effect on increasing individual taxpayer compliance partially and simultaneously. Meanwhile, the implementation of the E-Filling System and Tax Knowledge has a negative and insignificant effect on increasing the compliance of individual taxpayers partially.